2021
DOI: 10.1161/strokeaha.120.032979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Interventions on Health-Related Quality of Life After Stroke and Transient Ischemic Attack

Abstract: Exercise interventions have been shown to help physical fitness, walking, and balance after stroke, but data are lacking on whether such interventions lead to improvements in health-related quality of life (HRQoL). In this systematic review and meta-analysis, 30 randomized controlled trials (n=1836 patients) were found from PubMed, OVID MEDLINE, Web of Science, CINAHL, SCOPUS, The Cochrane Library, and TRIP databases when searched from 1966 to February 2020 that examine the effects of exercise interventions on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 79 publications
0
16
0
1
Order By: Relevance
“…This may suggest a larger proportion of cognitive/mental problems in this group, which may have been caused by the stroke, result from the lower premorbid function, a higher age and stroke severity, or a combination of these. Exercise interventions are known to have small to moderate beneficial effects on HRQOL in physical and mental health domains that diminish at longer-term follow up, and no significant effects on societal or participatory domains, (67). The limited uptake of physical activity after the intervention, as indicated by the activity monitoring at 12-weeks along with lower HRQOL-scores on cognitive/mental components, supports these notions.…”
Section: Discussionmentioning
confidence: 97%
“…This may suggest a larger proportion of cognitive/mental problems in this group, which may have been caused by the stroke, result from the lower premorbid function, a higher age and stroke severity, or a combination of these. Exercise interventions are known to have small to moderate beneficial effects on HRQOL in physical and mental health domains that diminish at longer-term follow up, and no significant effects on societal or participatory domains, (67). The limited uptake of physical activity after the intervention, as indicated by the activity monitoring at 12-weeks along with lower HRQOL-scores on cognitive/mental components, supports these notions.…”
Section: Discussionmentioning
confidence: 97%
“…This sample size supports a 20% tracking loss rate. We established a minimum effect size of 0.75 standard deviations by considering the results of meta-analyses studying the effects of mindfulness or PE on cognition or emotional wellbeing in stroke patients (e.g., Abbott et al, 2014 ; Oberlin et al, 2017 ; Ali et al, 2021 ; Sun et al, 2021 ). The effect sizes reported in these papers range from small-moderate (between d = 0.30 and d = 0.50) to moderate-large (between d = 0.50 and d = 1), depending on the intervention and the outcome studied.…”
Section: Discussionmentioning
confidence: 99%
“…In stroke patients, contrarily to the effects of mindfulness, the gains of PE on cognition and emotional wellbeing have been more thoroughly studied. Some meta-analyses of randomized controlled trials have shown small-to-moderate effects of PE on cognition ( Oberlin et al, 2017 ), depressive symptoms ( Eng and Reime, 2014 ), and post-stroke health-related quality of life ( Ali et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that exercise can improve cognitive function and activities of daily living in stroke patients (Li et al, 2022;Nindorera et al, 2022). Physical exercise is also effective in improving patients' quality of life and depressive symptoms after stroke (Ali et al, 2021;Zhang W. et al, 2021). However, there is still a lack of research on the mechanisms of exercise interventions for PSP.…”
Section: Introductionmentioning
confidence: 99%